Asimetrije dojk, strukturni nemir in zvezdaste lezije - Kocijančič, Igor (Radiology and oncology (Ljubljana), 1998)
The mammographic characteristics, differential diagnosis and additional diagnostic procedures in mammographic finding of architectural distortion, asymmetries and stellate lesions have been described. The correlation between clinical and mammographic findings has been pointed out. The development of malignoma is least possible in asymmetries, more probable in architectural distortion in combination with asymmetry and most possible in stellate lesions.
Keywords: Breast neoplasms; Diagnosis, differential; diagnostika; dojke; Mammography; novotvorbe; rak (medicina)